2002
DOI: 10.2331/fishsci.68.sup2_1537
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Na-gluconate on heat-induced gelation of salt-ground meat from walleye pollack

Abstract: The quality of kamaboko gel prepared from walleye pollack surimi with sodium gluconate (Na gluconate) was investigated in connection with the changes in myofibrillar protein accompanied with gelation. The gel stiffness of the kamaboko gel formed with Na-gluconate was higher than that with sorbitol at the same breaking strength, suggesting that the kamaboko gels with Na-gluconate were harder

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In general, the formation of non‐covalent bonding, especially intermolecular hydrophobic interaction, is postulated to depend on the denaturation process of protein. As a consequence of our preliminary research, 9 the possibility has emerged that suppression of myosin denaturation in salt‐ground surimi by Na‐gluconate may affect the physical properties of two‐step heated gel. A physico‐chemical approach to the effect of Na‐gluconate on thermal gelation of myosin 10 has also suggested that the increase of hydrated water stabilizes myosin and results in modification of gel formation.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In general, the formation of non‐covalent bonding, especially intermolecular hydrophobic interaction, is postulated to depend on the denaturation process of protein. As a consequence of our preliminary research, 9 the possibility has emerged that suppression of myosin denaturation in salt‐ground surimi by Na‐gluconate may affect the physical properties of two‐step heated gel. A physico‐chemical approach to the effect of Na‐gluconate on thermal gelation of myosin 10 has also suggested that the increase of hydrated water stabilizes myosin and results in modification of gel formation.…”
Section: Introductionmentioning
confidence: 96%
“…However, to elucidate the involvement of the suppression of myosin denaturation in salt‐ground surimi with rheological changes in heat‐induced gel on addition of Na‐gluconate, further extensive study including quantitative evaluation of changes in physical properties of two‐step heated gels in connection with myosin denaturation kinetics must be done. For example, since our previous results 9 were obtained only at a fixed level of Na‐gluconate in salt‐ground surimi , the dose dependency of the rheological parameters of two‐step heated gel as well as denaturation rates of myosin in salt‐ground surimi should be examined.…”
Section: Introductionmentioning
confidence: 99%